Epidemiology of periportal fibrosis and relevance of current Schistosoma mansoni infection within the context of repeated mass drug administration in rural Uganda: a population-based, cross-sectional study - Anjorin, Seun; Nabatte, Betty; Mpooya, Simon; Tinkitina, Benjamin; Opio, Christopher K; Kabatereine, Narcis B; Chami, Goylette F (Elsevier Ltd, 2024)
WHO guidelines for schistosomiasis-related morbidity control and elimination rely on current infection as a proxy indicator for morbidity. We evaluated these guidelines within the context of repeated mass drug administration and periportal fibrosis attributable to chronic intestinal schistosomiasis.BACKGROUNDWHO guidelines for schistosomiasis-related morbidity control and elimination rely on current infection as a proxy indicator for morbidity. We evaluated these guidelines within the context of repeated mass drug administration and periportal fibrosis attributable to chronic intestinal schistosomiasis.We examined 1442 households randomly sampled from 38 villages in Buliisa, Pakwach, and Mayuge districts of Uganda within the SchistoTrack cohort. Periportal fibrosis was diagnosed in 2834 individuals aged 5-90 years using ultrasound and image patterns C-F from the Niamey protocol. Schistosoma mansoni status and intensity were diagnosed by Kato-Katz microscopy and point-of-care circulating cathodic antigen tests. Schistosome infection, co-infections, and comorbidities were examined as exposures for periportal fibrosis. Multivariable logistic regressions were run with SEs clustered by household.METHODSWe examined 1442 households randomly sampled from 38 villages in Buliisa, Pakwach, and Mayuge districts of Uganda within the SchistoTrack cohort. Periportal fibrosis was diagnosed in 2834 individuals aged 5-90 years using ultrasound and image patterns C-F from the Niamey protocol. Schistosoma mansoni status and intensity were diagnosed by Kato-Katz microscopy and point-of-care circulating cathodic antigen tests. Schistosome infection, co-infections, and comorbidities were examined as exposures for periportal fibrosis. Multivariable logistic regressions were run with SEs clustered by household.Between Jan 6 and Feb 3, 2022, 342 (12·1%) of 2834 participants were diagnosed with periportal fibrosis. By Kato-Katz microscopy, 1229 (43·4%) of 2834 participants were infected. 1863 (65·7%) of 2834 participants had trace positive point-of-care circulating cathodic antigen tests, which was higher than prevalence by Kato-Katz microscopy, and 1158 (40·9%) of 2834 participants had trace negative point-of-care circulating cathodic antigen tests. Individual schistosome status, intensity, and prevalence of heavy intensity infections of less than 1% and less than 5% were not correlated with periportal fibrosis likelihood or village prevalence. Periportal fibrosis likelihood linearly increased with age from age 5 years to age 25 years, non-linearly increased from age 26 years to age 45 years, attenuated or remained unchanged from age 46 years to age 60 years, and steadily decreased past 60 years of age. History of liver diseases, HIV, and ultrasound-detected chronic hepatitis or early cirrhosis-like disease were associated with more than two-times increased periportal fibrosis likelihood.FINDINGSBetween Jan 6 and Feb 3, 2022, 342 (12·1%) of 2834 participants were diagnosed with periportal fibrosis. By Kato-Katz microscopy, 1229 (43·4%) of 2834 participants were infected. 1863 (65·7%) of 2834 participants had trace positive point-of-care circulating cathodic antigen tests, which was higher than prevalence by Kato-Katz microscopy, and 1158 (40·9%) of 2834 participants had trace negative point-of-care circulating cathodic antigen tests. Individual schistosome status, intensity, and prevalence of heavy intensity infections of less than 1% and less than 5% were not correlated with periportal fibrosis likelihood or village prevalence. Periportal fibrosis likelihood linearly increased with age from age 5 years to age 25 years, non-linearly increased from age 26 years to age 45 years, attenuated or remained unchanged from age 46 years to age 60 years, and steadily decreased past 60 years of age. History of liver diseases, HIV, and ultrasound-detected chronic hepatitis or early cirrhosis-like disease were associated with more than two-times increased periportal fibrosis likelihood.WHO guidelines reliant on current schistosome status and intensity are uninformative for identifying probable cases or communities with periportal fibrosis. History of HIV and underlying chronic hepatitis or early cirrhosis-like disease are risk factors that could be investigated for periportal fibrosis surveillance and management.INTERPRETATIONWHO guidelines reliant on current schistosome status and intensity are uninformative for identifying probable cases or communities with periportal fibrosis. History of HIV and underlying chronic hepatitis or early cirrhosis-like disease are risk factors that could be investigated for periportal fibrosis surveillance and management.NDPH Pump Priming Fund, Wellcome Trust, John Fell Fund, Robertson Foundation, and UK Research and Innovation Engineering and Physical Sciences Research Council.FUNDINGNDPH Pump Priming Fund, Wellcome Trust, John Fell Fund, Robertson Foundation, and UK Research and Innovation Engineering and Physical Sciences Research Council. MEDLINE - Academic